PEMANFAATAN MULSA DAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Ria Anggraeni; Abd. Hadid; Syamsuddin Laude (Universitas Tadulako, 2017)
This research aim was to determine the effect of various rates of chicken manure and straw mulch on the growth and yield of tomato plant. The research method used a Two-factorial Randomized Block design (RBD). The first factor was the rate of chicken manure consisting of 5 t/ha (P1), 10 t/ha (P2) and 15 t/ha (P3). The second factor was the rate of rice straw mulch including control (M0, without mulch), 5 t/ha (M1), 10 t/ha (M2) and15 t/ha (M3). Each treatment was repeated thrice, so that there were 36 experimental units. The results ofthe study indicated thatthe chicken manure and the rice straw mulch interaction significantly affected the growth and yield of tomato as observed on plant height, number of leaves, number of fruit per plant, yield per tile and yield per hectare. The interaction of chicken manure at 10 t/ha and rice straw mulch at10 t/ha resulted in largest number of leaves, number of fruit per plant, yield per tile and yield per ha.The highest production of tomatoes found was 11.98 t/ha. Keywords: Chicken manure, Rice straw mulch, and Tomato.